Impact of Covid-19 lockdown on sleep quality, physical activity, and body weight among university students: A retrospective cross-sectional study - Divya Vanoh; Allyanna Willma Juanis (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Covid-19 lockdown had caused lifestyle changes especially in sleep, physical activity, and body weight. Thus, this study aimed to determine the weight changes before and after the lockdown period and further assessed the association between sleep quality, physical activity, and body mass index (BMI). MATERIAL AND METHODS: This was a retrospective cross-sectional study involving 107 undergraduate students in Universiti Sains Malaysia. Subjects recalled information during the first lockdown implemented in Malaysia from early March 2020 to July 2020. The questionnaire consisted of socio-demography, anthropometry, and physical activity using International Physical Activity Questionnaire and sleep quality using Pittsburgh Sleep Quality Index. Chi-square analysis was used to determine the association between the variables using Statistical Package for Social Sciences software version 26.0. RESULTS: There was a significant increase of 1.8 kg in weight before and after the lockdown period. The majority of respondents had poor sleep quality (80.4%) and low physical activity (60.2%), respectively. Almost 29% of the subjects had sleep latency of more than 30 min while 69.1% of them had sleep duration of <7 h. There was no significant association between sleep quality and BMI as well as physical activity and BMI. CONCLUSION: Our study demonstrated that the prevalence of poor sleep quality and low physical activity among university students was high during Covid-19 confinement. Moreover, youths have a significant increase in body weight during the lockdown period. Thus, university students may adopt exciting leisure activities to keep themselves active such as doing meditation or joining online exercise classes.